SEISMIC ENERGY RELEASES FROM VOLCANOES - Yokoyama I. (My University, 1988)
Seismic energy release during the precursory, eruptive and declining stages of volcanic activities provides various information about the mechanisms of volcanic eruptions and the temporary developments of their activities. Hitherto the energy release patterns from precursory earthquake swarms were used to predict the eruption times, especially of andesitic or dacitic volcanoes. In this paper the discussion is expanded to quantify the total amount of seismic energy released at the threshold of volcanic eruptions, with reference to the results observed at several volcanoes. The results generally indicate that the cumulative seismic energy release from the precursory earthquake swarms exceed 101718ergs before eruptions at any andesitic or dacitic volvanoes. This allows the seismic efficiency, or the ratio of energy radiated seismically, and the energy required for the volumetric expansion to be estimated by incorporating available deformation data with the seismic data. The dependency of seismic efficiency on the type of volcanic activity, i. e. non-explosive outbreaks, phreatic and magmatic eruptions, dome formation, etc., was evaluated from observations at a few volcanoes that provided a variety of examples.